Linking international trade and transport - what are the determining factors? - Ole Kveiborg (European Regional Science Association (ERSA), 2005)
Historically there have been close relations between international trade and international transport. Development in trade is mirrored in the development in international transport. However, it is also well known that patterns of trade changes. The types of commodities that are traded today differ from the commodities that were traded ten years ago. Trade of services has increased and the trad-ing partners have changed. The opening of the European market towards Eastern Europe has changed the spatial pattern of where commodities are exported to and imported from. It is obviously not straightforward to tell how these changes influence the development in international transport. This paper investigates the impacts of some of the factors that play a role in the development of in-ternational freight transport. The included factors are trade of different commodities and countries, the weight of traded commodities, the model of transport and the weight of the conveyed goods. We do this using a decomposition method on Danish trade data over a period from 1988 to 2003 and a link from these data to data about international transports on heavy vehicles. We observe that the development in transport is composed of varying changes in the mentioned fac-tors of which some imply increasing transport and some imply declining transport. This finding in-dicates the importance of taking proper account of the various factors in modelling freight transport and the relation between freight and economic trade.
Keywords: 330